2010
DOI: 10.1586/edm.10.59
|View full text |Cite
|
Sign up to set email alerts
|

Specific dermatoses of pregnancy: advances and controversies

Abstract: Specific dermatoses of pregnancy include herpes (pemphigoid) gestationis, polymorphic eruption of pregnancy (also known as pruritic urticarial papules and plaques of pregnancy), prurigo of pregnancy and pruritic folliculitis of pregnancy. This article focuses on what is currently known about the epidemiology, clinical characteristics, etiopathogenesis and management of these disorders. Moreover, it discusses the intrahepatic cholestasis of pregnancy and 'atopic eruption of pregnancy', which were recently recla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 145 publications
0
19
0
Order By: Relevance
“…Pemphigoid gestationis (PG), previously known as herpes gestationis, is a rare autoimmune skin condition that affects between 1 in 10,000 and 1 in 50,000 pregnancies [1]. It is related to the pemphigoid skin disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pemphigoid gestationis (PG), previously known as herpes gestationis, is a rare autoimmune skin condition that affects between 1 in 10,000 and 1 in 50,000 pregnancies [1]. It is related to the pemphigoid skin disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnoses include other dermatoses of pregnancy, drug reaction, erythema multiforme (EM) and contact dermatitis [2]. Diagnosis is confirmed with lesion biopsy showing linear C3 deposition along the basement membrane zone [1][2][3]. Goals of treatment are to relieve symptoms, decrease further bullae formation, and promote healing of the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…It typically develops in the second quarter of pregnancy [1][2][3][4][5][6][7] , and the incidence rate is approximately 1 in 3,000 pregnancies. 7 Its etiology is uncertain, probably due to its rare ocurrence.…”
Section: Discussionmentioning
confidence: 99%
“…7 Its etiology is uncertain, probably due to its rare ocurrence. 1,6,7 A few studies on the subject have been conducted, and a few cases have been reported in the literature. It is believed that many cases are under-reported, as it is often confused with bacterial folliculitis .1,7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation